RETRACTED: The main indicators of body thickness, branch growth of intensive apple trees - Yunusov Rustam; Mavlonov Zavqiddin (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001